Genetic variation near the MC4R gene rs17782313 as a protective factor against high visceral fat: case control study in the Jambi Malay population - Alya Dwiva Juhari; Citra Maharani; Anggelia Puspasari; Rina Nofri Enis; Armaidi Darmawan (Published by Universitas Gadjah Mada, 2025)
Obesity is commonly assessed using the body mass index (BMI), which does not distinguish between fat and lean mass. Among fat distributions, visceral fat is more strongly associated with the risk of metabolic disease. Visceral or central obesity, characterized by excessive visceral fat accumulation, has become increasingly prevalent in recent years. Genetic factors, including rs17782313 polymorphism near the melanocortin 4 receptor (MC4R) gene, have been implicated in visceral fat accumulation. Previous studies reported varying effect sizes across different populations and inconsistent genotype-phenotype associations. However, no studies have investigated this association in the Jambi Malay Population. This case-control study aimed to evaluate the association between the MC4R rs17782313 polymorphism and visceral fat in the Jambi Malay population. A total of 110 Jambi Malay subjects participated in the study. Visceral fat was measured using bioelectrical impedance analysis (BIA), and genotyping was performed using the Tetra-ARMS PCR method. Bivariate and multivariate analyses were conducted to assess the association between genetic variation and visceral fat levels. Bivariate analysis showed that the TC genotype had a protective effect against high visceral fat compared to the TT genotype (p = 0.037; OR = 0.395). Similarly, the recessive model (CC+TC vs. TT) also indicated a protective effect (p = 0.022; OR = 0.375). In logistic regression model adjusted for calorie intake and physical activity, the protective effect persisted for both TC (p = 0.018; OR = 0.302) and the recessive model (p = 0.013; OR = 0.305). However, further adjustment for gender nullified the effect of the TC genotype, whereas the recessive model remained statistically significant, though the genetic effect was attenuated (p = 0.044; OR = 0.372). In conclusion, the TC genotype of MC4R rs17782313 is associated with a protective effect against visceral fat accumulation. This effect is influenced by calorie intake, physical activity, and gender.